Research on the Evaluation System of Green Highway Construction - Zhou, Qiang (International Journal of Natural Resources and Environmental Studies, 2024)
This paper studies the current situation of the development of green highways, analyzes the stages of the whole life cycle of green highways, and puts forward various evaluation indicators in the three stages of design, construction, operation and maintenance, which has certain reference value for the research of the evaluation system of green highways.